Evaluasi Sistem Pengendalian Manajemen Pemberian Kredit Pada Akasia Bank (PT BPR Amanat Kesejahteraan Indonesia) Kota Batu - Lis Lestari Sukartiningsih; Kirana Dewi Kristiani (Universitas Katolik Widya Karya Malang, 2023)
This research aims to evaluate the management control system for granting study credit at Akasia Bank (PT BPR Amanat Welfare Indonesia) Batu City. Data collection methods were carried out by observation, interviews and documentation, using primary data sources and secondary data. The problem that occurs is that the credit management control system at Akasia Bank is still weak. This is proven by the fact that there is still a dual function in the Account Officer section which is tasked with surveying and credit analysis. The reason is that the number of employees is still limited, resulting in the performance of the credit management control system being less than optimal. The results of the qualitative descriptive analysis by separating the Account Officer function into the survey section, the credit analysis section, by adding new employees to the Credit Analyst function, the credit granting system and procedures can be achieved in accordance with the company's objectives in safeguarding assets, records and documents to avoid mistakes made by irresponsible employees, so that the credit management control system can be effective and efficient.